Raising up to the climate challenge - Understanding and assessing farmers' strategies to build their resilience. A comparative analysis between Ugandan and Swiss farmers. (January 2022) - Le Goff, Ulysse; Sander, Adelaide; Lagana, Maria Hernandez; Barjolle, Dominique; Phillips, Suzanne; Six, Johan
Abstract: Climate change is a growing concern for farmers and food systems across the globe, raising interest in their resilience to climate change. Thus, exploring farm resilience in various contexts may help understand its prerequisites and build context and scale-specific strategies. Using an adaptive cycle framework through a survey-based assessment of the resilience of farmers in Uganda and Switzerland, we assessed farmers' resilience across a set of 13 behaviour-based indicators. Farm resilience appeared to be differently constructed in each context. While in Uganda, farmers maintain a high degree of resilience through local community interconnections and agroecological practices, Swiss farmers rely more on institutional support, high access to information and new technologies. Additionally, the self-perceived resilience proved to be strongly and positively correlated to the overall farm resilience, further supporting the potential for more participatory approaches. In a complex field where methodologies are numerous and contexts vary dramatically, flexible yet consistent tools based on participatory approaches may pave the way to context-specific recommendations to stakeholders to strengthen farming system resilience under different context found around the world. Highlights: Resilience assessments were carried on farming systems (FS) in different contexts. FS resilience appears to be differently constructed in different contexts. FS in Uganda maintain resilience through local interconnections and agroecology. Swiss FS rely more on institutions, high access to information and new technologies. The self-perceived resilience appeared to be positively correlated to resilience.